2019
DOI: 10.4236/ojap.2019.84007
|View full text |Cite
|
Sign up to set email alerts
|

Climatological Analysis of Aerosols Optical Properties by Airborne Sensors and in Situ Measurements in West Africa: Case of the Sahelian Zone

Abstract: This paper deals with the climatology of aerosols in West Africa based on satellite and in situ measurements between 2001 and 2016 and covers four sites in the Sahelian zone. There are indeed Banizoumbou (13.541˚N, 02.665˚E), Cinzana (13.278˚N, 05.934˚W), Dakar (14.394˚N, 16.959˚W) and Ouagadougou (12.20˚N, 1.40˚W) located respectively in Niger, Mali, Senegal and Burkina Faso. Thus, an intercomparison between the satellite observations and the in situ measurements shows a good correlation between MODIS and AER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The heavy aerosol layer is located around 1000 m asl during nighttime (Figure 3(j), Figure 3(k)). This strong attenuated backscatter signal indicates a tick aerosol layer, in agreement with Senghor et al [37], Adams et al [30], and Bado et al [42]. Léon et al [43] have observed from lidar measurements a thick aerosol layer located be-tween 1000 and 2000 m at the Western coastal of Dakar in September 2001.…”
Section: September To Novembersupporting
confidence: 82%
“…The heavy aerosol layer is located around 1000 m asl during nighttime (Figure 3(j), Figure 3(k)). This strong attenuated backscatter signal indicates a tick aerosol layer, in agreement with Senghor et al [37], Adams et al [30], and Bado et al [42]. Léon et al [43] have observed from lidar measurements a thick aerosol layer located be-tween 1000 and 2000 m at the Western coastal of Dakar in September 2001.…”
Section: September To Novembersupporting
confidence: 82%
“…An analysis of this figure allows us to locate aerosols in Burkina Faso in March with a maximum in the eastern part and in June marked by a massive presence of aerosols on the northern side. All this illustrates the effect of aerosol emissions in the Sahara probably due to the proximity of this area containing the main sources of dust [12]. These are located in the northern part of the country, more precisely in the northwestern part of Mali, and on the eastern side towards Niger, including Bodélé in Chad, which is considered the largest source of dust emissions in the world [9].…”
Section: Annual Cycles Of Aerosol Optical Thickness (Aod)mentioning
confidence: 88%
“…In addition, aerosol products supplied by SeaWiFS are mainly applicable and valid for oceanic regions [29] [30] and are available on NASA's website (https://giovanni.gsfc.nasa.gov/giovanni/). All these details about the SeaWiFS sensor are clearly provided by Nébon et al [12].…”
Section: Sea-viewing Wide Fiel-of-view Sensor (Seawifs)mentioning
confidence: 99%
See 2 more Smart Citations